Os limites da recuperação econômica da Zona do Euro (2008-2016) - Oliveira, Giuliano Contento de; Wolf, Paulo José Whitaker; Palludeto, Alex Wilhans Antonio (Brazilian Keynesian Review, 2016)
Since the outbreak of the global crisis in 2008, the countries of the periphery of the euro zone have faced great difficulties to enable the recovery of product, income and employment levels. The paper discusses this process and it argues that the exhaustion of conventional policies, along with the "genetic faults" of the single currency institutionality, contributes to impose sharp limits to the economic recovery process in many countries of the region.